UU Lingkungan Hidup dan Tindak Pidana Korporasi: Antara Regulasi dan Penegakan Hukum - Suminah; Mbunai, La Ode (Universitas Sains Indonesia Publishing, 2025)
This study discusses the legal analysis of environmental crimes in the context of the latest laws in Indonesia, specifically Law No. 32 of 2009 concerning Environmental Protection and Management and the accompanying regulatory changes until 2025. This study uses a normative juridical method with a statute approach and a conceptual approach. The data used are secondary data obtained from library studies, including laws and regulations, legal literature, and scientific journals. The main focus of this study is on the criminal liability of corporations as perpetrators of environmental crimes, as well as the challenges of legal implementation faced in practice. Although the legal framework is in place, law enforcement against corporations still faces structural, substantial, and cultural obstacles, including difficulties in proving corporate guilt and implementing the principle of ultimum remedium. This study highlights the importance of reforming the environmental legal system, increasing the capacity of law enforcement officers, and the need for policies that support environmental sustainability and ecological justice. With a comprehensive and equitable approach, it is hoped that the goals of sustainable development and the protection of the community's right to a good and healthy environment can be achieved.